Scientific production of Brazilian researchers focusing on oral surgery, oral medicine, and oral pathology - Lucyana Conceição FARIAS; Mauro Costa BARBOSA; Daniella Reis Barbosa MARTELLI; Hercílio MARTELLI JÚNIOR (Sociedade Brasileira de Pesquisa Odontológica, 2022)
Abstract We analyzed the distribution characteristics of the scientific production of Brazilian dentistry researchers of the Brazilian National Council for Scientific and Technological Development. The Lattes curriculum data of 211 researchers from Oral Pathology, Oral Surgery, and Oral Medicine fields were included (2018-2020). Over their academic career, 39 researchers published 7,555 papers (average, 175 articles/researcher); 3,876/7,555 papers were indexed in the Web of Science. During 2018-2020, 1,440/7,555 (19%) papers were published. Brazilian dental researchers contribute significantly to international research by participating in scientific journals' editorial boards, evaluating research promotion agencies, training researchers, and contributing to scientific and technological development.